Learning Model For Special Needs Children (ABK) in Inclusive Primary Schools - Rahmawati, Indriana; Basith, Abdul; Toba, Rostanti (Southeast Asian Journal of Islamic Education, 2021)
The learning process of students with special needs requires a model that adapts to the specificity of students. Therefore, the learning of students with special needs must be formulated by choosing the right model, so that the delivery of subject matter is well understood. So that education for students with special needs is met the same as students in general. This research was conducted to determine the learning model of students with special needs inclusive elementary schools in Gresik district, namely SDN 263 Gresik and SDN 13 Gresik. Data collection was carried out using interviews, observation, and documentation. There are seven primary data sources, including the head of the Gresik district resource center, the principal, the teacher in charge of the inclusion program, and the special companion teacher (GPK). The research was conducted for nine months, from July 2019 to April 2020. Qualitative was chosen as the research analyzer. The results of the study found that the use of the ABK learning model in the two schools is; a) Individual learning model, b) Pull out learning model or learning model in regular classes, c) Team teaching-learning model, d) Learning Model in the resource room, e) Modification of the learning curriculum.